C-Phycocyanin Extract Modulates Thermogenic and Inflammatory Markers in Brown Adipose Tissue of High-Fat Diet-Fed Animals - Artur Francisco Silva-Neto; Julia Ferreira Rocha; Gustavo Oliveira Lima; Juliana Miki Oguma; Vivien Cayres Giarola Suannes Pucci; Yasmin Alaby Martins Ferreira; Maria Isabel Alonso-Vale; Claudia Maria Oller do Nascimento; Mônica Marques Telles; Anna Rafaela Cavalcante Braga; Luciana Chagas Caperuto; Lila Missae Oyama (Molecules)
C-phycocyanin (CPC), a bioactive compound derived from Spirulina, has been described as a molecule with antioxidant and anti-inflammatory properties. It has also been demonstrated that sustainably obtained CPC effectively inhibited body mass gain, regulated serum leptin and resistin levels, and prevented the onset of a pro-inflammatory state in Swiss mice fed a hyperlipidic diet. These results highlighted the anti-obesogenic potential of CPC. Brown adipose tissue (BAT) has been identified as a promising target in the treatment of obesity, playing a role in energy expenditure. In this study, Swiss mice fed a high-fat diet were supplemented with 500 mg/kg body weight of CPC daily for 12 and 16 weeks. BAT was collected, and Western blot and ELISA were performed. A reduction in pro-inflammatory cytokines, as well as a decrease in leptin levels was observed in the tissue, which was also associated with a reduction in BAT relative weight to body mass. Furthermore, CPC administration was able to modulate uncoupling protein 1 (UCP1) levels, which is crucial in the thermogenesis process. Therefore, this study demonstrated that supplementation with CPC reduces inflammatory cytokines associated with detrimental effects in the BAT, emerging as a tool in combating obesity and improving BAT function.